Kajian Tentang Model Rencana Aksi Daerah Hak Asasi Manusia (Radham) Kabupaten Bondowoso Tahun 2018 - Khanif, Al, Dr.; Indrayati, Rosita; Ulum, Muhammad Bahrul; Wildana, Dina; Muhshi, Adam; Fadhilah, Nurul Laili; Satyaningtyas, Ayu Citra (UI Scholars Hub, 2019)
This article discusses Bondowoso District's regional human rights action plan (RADHAM) 2018. The focus of the 2018 RADHAM study explains the background and focus of Bondowoso's 2018 RADHAM policy as the basis for human rights-based policy making in the area. In the context of the division of power between the central and regional governments in the era of autonomy, human rights policy planning becomes complex because there are several regional and central policies that are mutually conflicting so that the mechanism for fulfilling human rights in the regions becomes complicated. To map this issue, local governments need a policy mechanism that focuses on mapping human rights issues that are used to determine the mechanism for solving problems and fulfilling human rights in their regions. This RADHAM policy will then be used as a reference for Bondowoso Regency to maximize the fulfillment of human rights in its territory.